Feedback Patterns of Excellent Teachers in Creating Thinking Culture in Classroom - Mohd Zhaffar, Nursafra; Rashed, Zetty Nurzuliana (SCAD Independent, 2022)
Although there is a growing interest in the culture of thinking in education, detailed information about classroom interaction that can incorporate thinking culture is lacking, particularly in the Malaysian context. Additionally, past studies do not focus on Islamic education. This study aimed to explore the feedback of excellent teachers in classroom interactions to incorporate a thinking culture. A qualitative case study approach was adopted on six excellent teachers (ETS) in Islamic Education using purposive sampling. Data were collected via teaching observation, semi-structured interviews, and document analysis. Thematic analysis revealed five themes that represented ETs’ feedback in classroom interactions to enhance thinking culture: give praise, give reprimand and criticism, stimulate information seeking, evaluate information, and ask for clarification. This study added value to the description of teachers’ feedback to create a thinking culture, especially in Islamic Education classrooms in Malaysia. The findings indicated that teachers need to increase open feedback, be willing to listen to students’ views, use praise and criticism selectively, and be a trustee of students for a democratic classroom to be realized. This study is expected to strengthen the effectiveness of teaching that incorporates a thinking culture.